Outcome of peroral endoscopic myotomy (POEM) in treatment-naive patients. A systematic review. (2nd January 2019) - Evensen, Helge; Kristensen, Vendel; Larssen, Lene; Sandstad, Olav; Hauge, Truls; Medhus, Asle W.
Abstract: Objectives: Achalasia is a primary motility disorder of the esophagus characterized by aperistalsis and failure of lower esophageal sphincter (LES) relaxation. Treatment of achalasia aims at reducing LES pressure. The common treatment modalities are laparoscopic Heller myotomy and pneumatic dilatation, but during the last decade, a promising treatment, per oral endoscopic myotomy (POEM), has been introduced. The aim of the present study was to perform a systematic review of the literature to assess the outcome of POEM in treatment-naive patients. Materials and methods: A systematic literature search in PubMed, Embase and Cochrane databases was performed using the terms 'Achalasia AND (POEM OR peroral endoscopic myotomy OR per-oral endoscopic myotomy)'. Inclusion criteria were: original article; English language; n  ≥ 20 with ≥90% treatment-naive patients; follow-up ≥3 months; and outcome evaluation of POEM including symptom score and objective tests. Exclusion criteria were: reviews and meta-analyses; pediatric data; duplicates; and articles with overlapping data material. Results: Of the 1641 articles identified, seven were included. The included studies all reported a short-term clinical success of >90%. Clinical success including post-POEM reflux was mainly estimated by symptom scorings. There were few procedure-related complications. Conclusions: The studies of treatment-naive patients indicate a high rate of clinical success. Nevertheless, a more systematic and standardized evaluation is recommended to improve the reports on outcome of POEM. The follow-up rate should be high and the evaluation protocol should include both symptom scoring and objective testing with predefined treatment goals.